The Sirt1 Activator SRT1720 Mitigates Human Monocyte Activation and Improves Outcome During Gram-Negative Pneumosepsis in Mice - Blot, Mathieu; Léopold, Valentine; de Beer, Regina; Florquin, Sandrine; Butler, Joe M.; van’t Veer, Cornelis; de Vos, Alex F.; van der Poll, Tom (International journal of molecular sciences, 2025)
Community-acquired pneumonia (CAP) is a leading cause of death, with mortality linked to an unbalanced host response. Sirtuin (Sirt)1, a histone deacetylase, regulating metabolism and epigenetics, may be fundamental in activating the innate immune response. Sirt1 mRNA expression was significantly reduced in monocytes from CAP patients (n = 76) upon admission compared to healthy controls (n = 42), with levels returning to normal after 30 days. Pharmacological activation of Sirt1 with SRT1720 decreased LPS- and K. pneumoniae-induced IL-6 release in primary human monocytes and decreased NF-κB activation in THP1 cells. In a mouse K. pneumoniae pneumosepsis model, SRT1720 strongly reduced neutrophil influx and degranulation markers in bronchoalveolar lavage fluid, lowered pulmonary concentrations of IL-6 and TNF-α, and reduced lung pathology scores. Simultaneously, it reduced neutrophil content in liver tissue and plasma transaminase levels, alongside a trend toward reduced liver necrosis. Plasma IL-6 and TNF-α were significantly lower in SRT1720-treated mice at 42 h. Finally, while SRT1720 did not impact bacterial loads in the lungs, it reduced bacterial burden in blood, with a similar trend observed in liver homogenates. In conclusion, the Sirt1 activator SRT1720 exerts anti-inflammatory effects on human monocytes, reduces local and systemic inflammation and organ injury, and diminishes bacterial dissemination in murine pneumosepsis.